Schick, Teaching History With A Computer - A Complete Guide For College Professors - Allen, Calvin (Teaching History: A Journal of Methods, 1992)
James Schick is the founder and editor of the History Microcomputer Review. While this book is certainly not the first to deal with computers and history and is not really "A Complete Guide," it does go beyond the "number crunching" applications of quantitative history and provides excellent explanations of a wide range of uses from writing. to study aids, to programming.